The fruitless gene is required for the proper formation of axonal tracts in the embryonic central nervous system of Drosophila. - Song, H; Billeter, J; Reynaud, E; Carlo, T; Spana, E; Perrimon, N; Goodwin, S; Baker, B; Taylor, B (2002)
The fruitless (fru) gene in Drosophila melanogaster is a multifunctional gene that has sex-specific functions in the regulation of male sexual behavior and sex-nonspecific functions affecting adult viability and external morphology. While much attention has focused on fru's sex-specific roles, less is known about its sex-nonspecific functions. We have examined fru's sex-nonspecific role in embryonic neural development. fru transcripts from sex-nonspecific promoters are expressed beginning at the earliest stages of neurogenesis, and Fru proteins are present in both neurons and glia. In embryos that lack most or all fru function, FasII- and BP102-positive axons have defasciculation defects and grow along abnormal pathways in the CNS. These defects in axonal projections in fru mutants were rescued by the expression of specific UAS-fru transgenes under the control of a pan-neuronal scabrous-GAL4 driver. Our results suggest that one of fru's sex-nonspecific roles is to regulate the pathfinding ability of axons in the embryonic CNS.